Pengaruh Korean Wave, Brand Ambassador Dan Brand Image Terhadap Keputusan Pembelian Pada Produk Skincare Azarine - Fitriyani, Anggi; Nuryanto, Imam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Purchasing decisions are the final step through consideration of factors that drive consumers to buy products. The purpose of this study is to examine the influence of several focused factors, namely the Korean wave, brand ambassador and brand image on purchasing decisions for Azarine’s products. This study uses quantitative methods. Data collection techniques by distributing questionnaires online and offline with a sample of 100 respondents. The analysis technique uses SmartPLS 4.0 with the results of the study showing that the Korean wave does not have a significant influence on purchasing decisions, brand ambassadors have a significant influence on purchasing decisions and brand image has a significant influence on purchasing decisions. Keywords: korean wave, brand ambassador, brand image, purchase decision